2019
DOI: 10.1007/s10198-019-01064-z
|View full text |Cite
|
Sign up to set email alerts
|

Patient experiences with outpatient care in Hungary: results of an online population survey

Abstract: Background Health systems are undertaking efforts to make health care more patient centered and value based. To achieve this goal, the use of patient-reported experience measures (PREMs) is increasing, especially across OECD countries. However, in Hungary, data on patients’ experiences are still lacking. Thus, our aim was twofold: first, to collect data on outpatient experience in Hungary on patient–doctor communication and patient involvement in decision making and compare it with that of other O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…For example, patients in Ghana have reported opting-out of care in their nearby and designated facilities due to negative experiences (Bayuo 2017). Other studies have identified other determinants of negative patient experience such as age, with younger patients being more likely to perceive a negative experience (Brito Fernandes et al 2019;Xie et al 2019). There were no significant results regarding this in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, patients in Ghana have reported opting-out of care in their nearby and designated facilities due to negative experiences (Bayuo 2017). Other studies have identified other determinants of negative patient experience such as age, with younger patients being more likely to perceive a negative experience (Brito Fernandes et al 2019;Xie et al 2019). There were no significant results regarding this in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A first study focused on forgone medical visits as an important factor of patient-centric care (Lucevic et al 2019), examining questions regarding the existence of unmet medical needs if patients: (1) reported forgone medical visits due to costs; (2) forgone medical tests and treatment due to costs; (3) unfilled prescriptions for medicine, or skipped doses due to costs; (4) forgone medical visits due to difficulties in travelling. In addition, another study focused on the care experiences of the last outpatient consultation: (1) did the doctor spend enough time with the patient in consultation; (2) did the doctor provide easy to understand explanations; (3) did the doctor give the opportunity to ask questions or raise concerns about care or treatment; (4) did the doctor involve the patient in decisions about care and treatment (Brito Fernandes et al 2019). Both studies were important in emphasizing the need to collect, analyse and report on these patient-reported data in Hungary, in a consistent manner over time, and to allow cross-national comparisons with other OECD countries, where the same standardised questions have been used.…”
Section: Patient Experiences Of Carementioning
confidence: 99%
“…The survey Patient experiences in health care consisted of three main modules: 'eHealth literacy', 'Shared decision-making' and 'Patient-reported experience measures', which are detailed in full elsewhere [8,9,18,19]. The latter included a discrete choice experiment (DCE) to elicit respondents' preferences for aspects of the care experience in outpatient settings.…”
Section: Instrument Designmentioning
confidence: 99%
“…In Hungary, recent applications of the OECD's set of recommended PREMs are detailed in two articles: one sought to measure experiences of care in outpatient settings [9]; and the other focused on unmet health care needs due to cost and difficulties in travelling [8]. However, to measure those aspects of the care experience is only a first key layer in developing more targeted patient-centered policies.…”
Section: Introductionmentioning
confidence: 99%
“…As important areas of patient satisfaction, Jenkinson et al (2002) classifies i -physical comfort, ii -emotional support, and iii -respect for patient preferences. Several studies highlight patients' perception of how their care is provided and the positive patient experiences as an assessment of the quality of healthcare (Fernandes et al, 2019;Ahmed et al, 2014;Doyle et al, 2013;Price et al, 2014). Results by Ko et al (2019) provide strong empirical evidence that operational healthcare inefficiency negatively influences patient satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%